Incidental detection of a virilizing Sertoli-Leydig cell tumor during cesarean section: A case report - Roza Mahyoob; Keisuke Sugita; Akiko Yamamoto (Case Reports in Women's Health)
Sertoli-Leydig cell tumors are a rare type of sex cord-stromal tumors that are mostly hormonally active (androgenic or estrogenic). Owing to the rarity of this disease, its impact on pregnancy is not fully understood. This report concerns a rare case of a Sertoli-Leydig cell tumor incidentally discovered during a cesarean section. In a resource-poor setting, a 21-year-old woman was referred to hospital for her first childbirth. She had clitoromegaly for a few years, had never had a gynecological consultation, and had not received antenatal care during this pregnancy. Three hours after admission, an emergency cesarean section was indicated because of fetal distress. During the procedure, a right ovarian tumor measuring approximately 10 × 10 cm was found. Considering the patient's age and obstetric history, and the inability to perform histological evaluation during surgery at the hospital she attended, the decision was made to proceed only with tumor resection. Considering the possibility of a sex-cord stromal tumor focusing on the clitoromegaly, histopathological evaluation was performed, and a diagnosis of a Sertoli-Leydig cell tumor was obtained. This case underscores the importance of clinical vigilance for rare hormonally active ovarian tumors during pregnancy, particularly in low-resource settings.